Роль умов соціалізації в розвиненні соціального інтелекту особистості - Харченко, С. В.; Kharchenko, S. V.; Svitlana Kharchenko (Право і Безпека. - 2016. - № 2 (61). - С. 146–151, 2016)
З метою узагальнення уявлень про соціальні чинники, які впливають на формування соціального інтелекту як основи соціального пізнання особистості, розглянуто особливості сімейних стосунків, які сприяють розвитку соціального інтелекту; описано методи, які використовуються в освітніх закладах щодо розвитку соціального інтелекту в різні періоди онтогенезу, в тому числі й на етапі професійної підготовки. Визначено чинники, які перешкоджають формуванню або заважають оптимальному функціонуванню соціального інтелекту особистості.

In order to generalize ideas about social factors that influence the development of personality’s social intelligence as the basis of social cognition, the author has studied the research of characteristics of family relationships and methods of educational environment that contribute to the development of social intelligence in different periods of ontogeny. It has been demonstrated that certain stages of socialization are the most important components for the formation of personality’s social intelligence. The author has generalized the means of active learning (psychological and gymnastics exercises, training and cognitive tasks, role-playing and simulation games, social and psychological training, movie training, formed reading activities, etc.), offered by scholars for the development of social intelligence. The author has considered measures of professional training at Universities to create conditions for improving the abilities of social intelligence within specialists in a number of specialties. The results of studies focused on the effects of socio- and ethno-cultural conditions on the formation of personality’s social intelligence and on studying social intelligence within offenders have been outlined. Particular attention is paid to factors that prevent the formation or interfere to the proper functioning of personality’s social intelligence such as: social derivation, communication in the «distorted» environment, the impact of mass media and means of communication. It has been proved that the level of social intelligence is associated with certain socio-cultural life factors of the subject: residence, features oft education and social status of parents, learning content and experiences of diverse activities as the main condition for its development. It has been demonstrated that for the full development of personality’s social intelligence it is needed to organize in a certain manner acquisition of social experience and practice of social interactions by a person. It has been noted that the impact of conditions of professional activity on the nature of changes of social intelligence of a subject has not been enough studied. The attention is paid that the role of art in the development of social intelligence is not studied.

С целью обобщения представлений о социальных факторах, влияющих на формирование социального интеллекта личности как основы социального познания личности, рассмотрены особенности семейных отношений, которые содействуют развитию социального интеллекта; обобщены методы, использующиеся в образовательных заведениях относительно развития социального интеллекта в разные периоды онтогенеза, в том числе и на этапе профессиональной подготовки. Определены факторы, которые препятствуют формированию или мешают оптимальному функционированию социального интеллекта личности.
The role of socialization in terms of the development of personality’s social intelligence
Роль условий социализации в развитии социального интеллекта
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; соціальний інтелект; спілкування; соціалізація; методи розвитку; social intellect; communication; socialization; methods of development; социальный интеллект; общение; социализация; методы развития